2015
DOI: 10.1016/j.molp.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Defense Hormones in the Regulation of Ozone-Induced Changes in Gene Expression and Cell Death

Abstract: Apoplast, the diffusional space between plant cell plasma membranes, is an important medium for signaling within and between the cells. Apoplastic reactive oxygen species (ROS) are crucial signaling molecules in various biological processes. ROS signaling is interconnected with the response to several hormones, including jasmonic acid (JA), salicylic acid (SA) and ethylene. Using ozone (O3) to activate apoplastic ROS signaling, we performed global and targeted analysis of transcriptional changes and cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 111 publications
1
73
0
Order By: Relevance
“…However, nearly all of these overlapping genes also were present in the 3-h cat2 study (102 DEGs), suggesting that elevated transcript levels of these genes are not restricted to early 1 O 2 signaling. Besides the cat2 and flu experiments, O 3 RNA-Seq studies (Xu et al, 2015a(Xu et al, , 2015b) also were highly consistent with our transcriptional footprints. For instance, induced genes of the ROS cluster V footprint Figure 7.…”
Section: Ros Transcriptional Footprints Are Found In Environmental Stsupporting
confidence: 87%
See 4 more Smart Citations
“…However, nearly all of these overlapping genes also were present in the 3-h cat2 study (102 DEGs), suggesting that elevated transcript levels of these genes are not restricted to early 1 O 2 signaling. Besides the cat2 and flu experiments, O 3 RNA-Seq studies (Xu et al, 2015a(Xu et al, , 2015b) also were highly consistent with our transcriptional footprints. For instance, induced genes of the ROS cluster V footprint Figure 7.…”
Section: Ros Transcriptional Footprints Are Found In Environmental Stsupporting
confidence: 87%
“…were more than 90% present in O 3 treatments performed in multiple Arabidopsis accessions (Xu et al, 2015a(Xu et al, , 2015b, as shown in Supplemental Figure S7. Hence, our footprints also can be implemented on data obtained from RNA-Seq and support the biological relevance of our meta-analysis results.…”
Section: Ros Transcriptional Footprints Are Found In Environmental Stmentioning
confidence: 88%
See 3 more Smart Citations